MANAGERIAL SKILL IN IMPROVING THE EXCELLENCE OF LEARNING - Karwanto . (Edusentris, 2016)
This research reveals deeply managerial skill in improving learning excellence at three excellent senior high schools in Semarang, which have different characteristics. This research used a qualitative approach along with multi-case study design. Techniques of the data collecting include deep interview, observation on participation, along with documentation study. Data credibility checking used triangulation technique, checking the members, and discussion with associates. Data auditable checking of the research was performed by the supervisors and independent auditort. The collected data will be organized, interpreted, and analyzed repeatedly, both through analysis in case and analysis inter-case in order to arrange concept and abstract of the research’s findings. Results of the research show: (1) learning excellence characteristics at three Excellent Senior High Schools in Semarang; (2) Second, the principal’s skills in designing improved learning excellence are determined by prominent skills of the principal, which include skill in managing organizational change, monitoring each change, good skill in designing, and allocating human resources precisely. (3) the principal’s skill in implementing excellent improvement is proven through outcomes of his/her work, which can be seen from both academic and non-academic achievements of the students(4) the principal’s skills in evaluating result of the improved learning excellence during his/her leadership in making good progress for his/her school, creating conducive climate, making a progress in academic field and other prominent skills.ABSTRAKPenelitian ini bermaksud mengungkap lebih mendalam tentang keterampilan manajerial peningkatan keunggulan pembelajaran pada tiga SMA Unggulan di Kota Semarang yang memiliki karakteristik berbeda. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi multi kasus. Teknik pengumpulan data menggunakan wawancara mendalam, observasi berperan serta dan studi dokumentasi. Pengecekan kredibilitas data dilakukan dengan teknik triangulasi, pengecekan anggota, dan diskusi teman sejawat. Sedangkan pengecekan auditabilitas data penelitian dilakukan oleh para pembimbing dan independent auditor. Data yang terkumpul melalui ketiga teknik tersebut diorganisasi, ditafsir, dan dianalisis secara berulang-ulang, baik melalui analisis dalam kasus maupun analisis lintas kasus guna menyusun konsep dan abstraksi temuan penelitian. Hasil penelitian menunjukkan: (1) keunggulan pembelajaran ditemukan pada tiga SMA; (2) keterampilan kepala sekolah dalam perencanaan peningkatan keunggulan pembelajaran yang menonjol dalam: keterampilan memanaj perubahan organisasi, memonitor setiap perubahan, keterampilan merancang yang baik, dan mengalokasikan sumber daya manusia dengan tepat; (3) keterampilan kepala sekolah dalam pelaksanaan peningkatan keunggulan pembelajaran dibuktikan dengan hasil dari unjuk kerjanya melalui perolehan prestasi akademik dan prestasi non-akademik yang dicapai siswa; (4) keterampilan kepala sekolah dalam evaluasi hasil peningkatan keunggulan pembelajaran yang menonjol dalam: memonitor implementasi kebijakan pembelajaran, membina, mengarahkan dan memberdayakan guru dengan baik dalam melakukan evaluasi serta keterampilan dalam memonitor kemajuan belajar siswa.